2002
DOI: 10.1074/jbc.m203205200
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Mre11 Does Not Affect VSG Gene Duplication Mediated by Homologous Recombination in Trypanosoma brucei

Abstract: We demonstrate, by gene deletion analysis, that Mre11 has a critical role in maintaining genomic integrity in Trypanosoma brucei. mre11 ؊/؊ null mutant strains exhibited retarded growth but no delay or disruption of cell cycle progression. They showed also a weak hyporecombination phenotype and the accumulation of gross chromosomal rearrangements, which did not involve sequence translocation, telomere loss, or formation of new telomeres. The trypanosome mre11 ؊/؊ strains were hypersensitive to phleomycin, a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 72 publications
(84 reference statements)
8
63
1
Order By: Relevance
“…MSH2 and MLH1 mutants for assaying VSG switching were made in strain 3174, 2 a derivative of MITat1.2a (47). Determination of VSG switching frequency and pattern has been described previously (16,19,20). To assay the effect of base mismatches on recombination, MITat1.2a cells were transformed with the construct pTHT (43,44); targeting of the HYG gene (see text) to the tubulin array was confirmed by Southern mapping with KpnI-or EcoRI-digested genomic DNA (data not shown).…”
Section: T Brucei Strains and Growth-t Bruceimentioning
confidence: 99%
See 1 more Smart Citation
“…MSH2 and MLH1 mutants for assaying VSG switching were made in strain 3174, 2 a derivative of MITat1.2a (47). Determination of VSG switching frequency and pattern has been described previously (16,19,20). To assay the effect of base mismatches on recombination, MITat1.2a cells were transformed with the construct pTHT (43,44); targeting of the HYG gene (see text) to the tubulin array was confirmed by Southern mapping with KpnI-or EcoRI-digested genomic DNA (data not shown).…”
Section: T Brucei Strains and Growth-t Bruceimentioning
confidence: 99%
“…Consistent with this genetic analysis, inactivation of KU70 or KU80, which catalyze a non-homologous end-joining pathway of DNA repair in other organisms (17,18), does not affect VSG switching (19). Surprisingly, mutation of MRE11 also does not affect VSG switching (20), despite this gene encoding an enzyme that has been proposed to have many roles in homologous and non-homologous recombination (21).…”
mentioning
confidence: 99%
“…Moreover, though a later study confirmed that ISceI-mediated DSB formation can activate switching in a BES location-dependent fashion, strict localization of breaks within the active BES and around the 70-bp repeats was not confirmed, and instead ligation-mediated PCR suggested that all BES are fragile adjacent to the telomere (128). Finally, as noted above, the lack of a role for MRE11 in VSG switching is perplexing, given its central function in DSB detection and repair (152). One explanation for these inconsistencies, as we have argued throughout, is that VSG recombination cannot be explained by a single mechanism, or by a sequence to direct that mechanism, and the system acts flexibly through several routes.…”
Section: How Is T Brucei Vsg Switching By Recombination Initiated?mentioning
confidence: 98%
“…Understanding where this process occurs would be very revealing: are the array VSG pseudogenes "assembly intermediates" that arise from ongoing subtelomeric recombination, or might the reaction be rapid enough to allow assembly within the active BES without leading to protracted expression of nonfunctional VSG protein (87)? Loss of array VSGs during growth of T. brucei BRCA2 and MRE11 mutants hints at recombination within the subtelomeres, but the nature and scale of such events is unclear (109,137,152).…”
Section: Segmental Gene Conversion Produces Functional Vsg Surface Coatsmentioning
confidence: 99%
See 1 more Smart Citation